A blockchain‐enabled framework for sharing logistics resources during emergency operations. Issue 3 (18th December 2020) - L'Hermitte, Cécile; Nair, Nirmal‐Kumar C.
Abstract : This study presents conceptual research designed to assess how the sharing economy concept can be leveraged to increase the participation of commercial organisations, such as retailers and transporters, in disaster relief operations. Drawing on social exchange theory, the academic literature on the sharing economy and blockchain, as well as existing resource‐sharing practices in commercial and humanitarian logistics, the study develops a theoretical framework for analysing the structure, benefits, and prerequisites of a logistics‐sharing system in emergency response. In addition, it proposes to utilise the blockchain distributed ledger technology—a shared data platform that enables authenticated communication and the widespread sharing of real‐time information—to facilitate interactions and enhance trust between emergency responders and commercial organisations. It is argued that using commercial logistics resources, including emergency supplies, transport capacity, and storage space, has the potential to improve the mobilisation and deployment of urgently needed relief items and augment the flexibility of emergency response.